2012
DOI: 10.1542/peds.2012-0444
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study of Children With Bronchiolitis Requiring Mechanical Ventilation

Abstract: In this multicenter study of children hospitalized with bronchiolitis, we identified several demographic, historical, and clinical factors that predicted the use of CPAP and/or intubation, including children born to mothers who smoked during pregnancy. We also identified a novel subgroup of children who required mechanical respiratory support <1 day after respiratory symptoms began.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 66 publications
4
119
1
4
Order By: Relevance
“…16,28 Our decision to use <90% as a threshold is based on the latest American Academy of Pediatrics recommendation 1 and on recent evidence revealing comparable outcomes in patients discharged with a saturation threshold of 90% vs 94%. 58 Interestingly, duration of symptoms was not associated with escalated care in this study.…”
Section: Figurementioning
confidence: 99%
“…16,28 Our decision to use <90% as a threshold is based on the latest American Academy of Pediatrics recommendation 1 and on recent evidence revealing comparable outcomes in patients discharged with a saturation threshold of 90% vs 94%. 58 Interestingly, duration of symptoms was not associated with escalated care in this study.…”
Section: Figurementioning
confidence: 99%
“…These variables were chosen based on clinical plausibility and a priori knowledge. 4,5,27 We did not control for breastfeeding status because it was considered an ancestor variable of the association of interest (ie, the relationship between breastfeeding and likelihood of bronchiolitis may be mediated by gut microbiota), and adjustment of an ancestor variable would bias the inference toward the null.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Two large prognostic studies have also identified retractions as predictors of severe disease in ED and hospitalized patients. 31,32 Decisions regarding hospitalization and length of stay in the ED are multifactorial. Nonrespiratory severity parameters (eg, feeding), prognostic factors (eg, age), social issues, clinical judgment, available resources, and local practices influence decisionmaking.…”
Section: 18mentioning
confidence: 99%